2008
DOI: 10.1177/0047287508328792
|View full text |Cite
|
Sign up to set email alerts
|

Residents' Perceptions towards the Impacts of the Beijing 2008 Olympic Games

Abstract: The aim of this article is to identify and examine the host residents' perceptions towards a mega event, the Beijing 2008 Olympic Games, and its impacts. An impact scale comprising 20 impact items with four factors—social-psychological impacts, urban development impacts, economic development impacts, and social life impacts—was developed. It was found that the majority of respondents perceived the impacts of the 2008 Games very positively, particularly for those related to the social-psychological, urban devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
255
5
27

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(304 citation statements)
references
References 31 publications
17
255
5
27
Order By: Relevance
“…The difference between the current investigation and previous ones (e.g., Zhou &Ap, 2009) is that in our research we test the mediator role of expectations of positive legacies between the work of the organizers and support. That is, people's decision to support the event is affected not only by the work of the organizers done in preparing for it, but also by something that is supposed to stay after the event and make life in the hosting community better.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…The difference between the current investigation and previous ones (e.g., Zhou &Ap, 2009) is that in our research we test the mediator role of expectations of positive legacies between the work of the organizers and support. That is, people's decision to support the event is affected not only by the work of the organizers done in preparing for it, but also by something that is supposed to stay after the event and make life in the hosting community better.…”
mentioning
confidence: 81%
“…These duties include construction of sport venues, transportation improvement, means of communication improvement, security strategies, and personnel recruitment, selection and training. In previous investigations, residents' evaluations of the work of the organizers in preparation to host sport mega-events have affected their support intentions(e.g., Zhou & Ap, 2009). In the current investigation, we also expect support for the event to be a positive reciprocity whenever the residents perceive the work of the organizers as somehow positive and beneficial for themselves and for their communities.…”
Section: The Work Of the Organizersmentioning
confidence: 99%
See 1 more Smart Citation
“…The size and type of each event varies, as does the host community's industrial and social development size of the destination and political regime (Baker, 2004;Fredline, 2005). Zhou and Ap's (2008) study on the Beijing Olympics identified that residents' support for the Games was very high despite the fact that 93% of those surveyed were not consulted in the planning process, a factor not necessarily acceptable in a less centralized society. This point is borne out by Pranic et al's (2012) study of the 2009 World Men's Handball Championship in Croatia.…”
Section: Promotion Of Travel Advice To Businessesmentioning
confidence: 99%
“…2013). Spor organizasyonları-nın yukarıda belirtilen bütün bu önemine ve değe-rine rağmen, etkinliklerin düzenlendiği yerlerde yaşayan halkın, bu tür organizasyonlara karşı algı-ları ve tutumları göz ardı edilmiştir (Zhou ve Ap 2009). Turizmle ilgili olarak, yerel halk için önemli olan nokta, turizmin o şehirde yaşayanların kişi-sel yaşamları üzerine olan etkisidir (Alaeddinoğlu 2007).…”
Section: Oli̇mpi̇yat Oyunlariunclassified